Answer:
![\large\boxed{y-3=-(3)/(8)(x+2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4yhupx3182x86tqh8fj6xcpdsu85qaqp5b.png)
Explanation:
Ths point-slope form of an equation of a line:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lwv5ftdd36i4idvu50qxfdgwxhdby4wlt5.png)
m - slope
(x₁, y₁) - point
We have the equation:
![y-3=(8)/(3)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cz1nkb786sjd88p0tfvtpbwjk0nxubp41l.png)
Therefore the slope is
![m=(8)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/732k2se4mvjvff2bhiwrl097imo0l0ir3s.png)
Let k: y = m₁x + b₁ and l: y = m₂x + b₂.
l ⊥ k ⇔ m₁m₂ = -1 ⇒ m₂ = -1/m₁
Therefore
![m_1=(8)/(3)\Rightarrow m_2=-(1)/((8)/(3))=-(3)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lg1v4wcmyct0lzg67h690rc023upc0f8wi.png)
The line passes throguh the point (-2, 3).
We have the equation in point-slope form:
![y-3=-(3)/(8)(x-(-2))\\\\y-3=-(3)/(8)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/okvo5zcspfnk83804jokv1ouzps1r7562b.png)